Osteosarcoma journey over two decades in India: Small steps, big changes. Issue 9 (17th June 2019) - Bajpai, Jyoti; Chandrasekharan, Arun; Simha, Vijai; Mandal, Tanmoy; Shah, Kajal; Hingmare, Sachin; Rangarajan, Bharath; Shetty, Nishitha; Vora, Tushar; Ghosh, Jaya; Rekhi, Bharat; Banavali, Sripad; et al.
Abstract: Background: The management of osteosarcoma is challenging especially in lower‐income and middle‐income countries, and there is an unmet need to evolve efficient and sustainable chemotherapy regimens. Methods: We compared the outcomes in nonmetastatic osteosarcoma patients treated with three sequential non‐high‐dose methotrexate‐based combination chemotherapy protocols at a single tertiary care center over two decades. The first protocol, OGS‐99, involved dose‐intense, alternating dyads of three drugs: doxorubicin (Dox), cisplatin (CDDP), and ifosfamide (Ifo). The second protocol, OGS‐99 enhanced, included OGS‐99 drugs with etoposide and enhanced supportive care. The OGS‐12 protocol involved dose‐dense administration of eight sequential dyads of Dox, CDDP and Ifo, universal growth factor prophylaxis and targeted nutritional support. Event‐free survival (EFS), overall survival (OS), and toxicity were reported using a retrospective chart review in the OGS‐99 and OGS‐99 enhanced protocols and prospectively in the OGS‐12 protocol. Results: A total of 41, 94, and 385 treatment‐naïve, consecutive, nonmetastatic patients with extremity osteosarcoma were treated with the OGS‐99 (2000–2005), OGS‐99 enhanced (2010), and OGS‐12 (2011–2016), respectively. At a median follow‐up of 19, 86, and 39 months, the five‐year EFS rates were 38%, 50%, and 62% in the OGS‐99, OGS‐99 enhanced, and OGS‐12, respectively. The corresponding rates of five‐year OS were nonevaluable, 60% and 77%, respectively, with acceptable rates of grade 3–4 toxicities: febrile neutropenia (40%), thrombocytopenia (36%), anemia (51%), and 1% deaths related to toxicity. Conclusions: Sequential selection of an intelligent, dose‐dense chemotherapy regimen together with enhanced supportive care resulted in marked improvement in outcomes of nonmetastatic osteosarcoma and this "small steps—big changes" model deserves wider recognition and usage.